GAS TURBINE SUITABLE FOR THE AMBIENT CONDITIONS PREVAILING IN ARAB GULF COUNTRIES - A PROGNOSTIC ANALYSIS - Antipov, Y. A.; Al-Rubaiawi, Majid Sabbar Salih Al-Rubaiawi; Frolov, Mikhail (Journal of Applied Engineering Science, 2023)
The present study conducted a prognostic analysis with the aim of understanding the problems associated with the operation of gas turbines in hot climatic regions like the Middle Eastern region. In addition to the hot and dry climatic condition, the region experiences frequent dust storms which can result in operational problems, shorter life span and very high maintenance costs, making air filtration a mandatory operation. Due to this condition and taking into consideration the high humidity of the coastline region, for better effective operation, longer useful life and reduced operating cost the gas turbines have to be located away from the coastline region. To get better power output from the gas turbines, the ambient air has to be cooled. Among the different options available for cooling, evaporative cooling system was found to be more suitable and cost effective for the region. Analysing the performance of the gas turbine, it was found that adopting the cooling system will result in enhancing the output power up to 7.12%.
Keywords: gas turbine, ambient conditions, biobased fuels, power generation